Спроба класифікації пам’яток археології ранньомодерного часу на Волині - Верба, Т. В.; Verba, Taras (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто питання класифікації пам’яток археології ранньомодерного часу. Висвітлено основні способи класифікації, прийняті в археологічних школах різних країн. Перераховано типи пам’яток XVI-XVIII ст., які трапляються на території Волинської області, та здійснено спробу їх класифікації.The article is focused on the question of classification early modern period archaeological monuments. The author highlights the major classification systems adopted in archaeological schools in different countries. The main types of monuments of XVI-XVIII centuries, which are found in Volyn oblast were listed and was carried an attempt of their classification. Considering that the history of early modern period remained a significant number of written sources which often contain information about the purpose and nature of monuments, it was chosen functional classification for systematization.
An Attempt of Classification Early Modern Period Archaeological Monuments in Volyn Region
Keywords: археологія; ранньомодерний час; пам’ятка; класифікація; Волинь; archaeology; early modern period; classification; Volyn